Controversies with self-emulsifying drug delivery system from pharmacokinetic point of view. (21st November 2016) - Chatterjee, Bappaditya; Hamed Almurisi, Samah; Ahmed Mahdi Dukhan, Ather; Mandal, Uttam Kumar; Sengupta, Pinaki
Abstract: Self-emulsifying drug delivery system (SEDDS) is an isotropic mixture of lipid, surfactant and co-surfactant, which forms a fine emulsion when comes in contact of an aqueous medium with mild agitation. SEDDS is considered as a potential platform for oral delivery of hydrophobic drug in order to overcome their poor and irregular bioavailability challenges. In spite of fewer advantages like improved solubility of drug, bypassing lymphatic transport etc., SEDDS faces different controversial issues such as the use of appropriate terminology (self-microemulsifying drug delivery system; SMEDDS or self-nanoemulsifying drug delivery system; SNEDDS), presence of high amount of surfactant, correlation of in vitro model to in vivo studies, lack of human volunteer study and effect of conversion of SEDDS to final administrable dosage form on pharmacokinetic behavior of the drug. In this review, potential issues or questions on SEDDS are identified and summarized from the pharmacokinetic point of view. Primarily this review includes the conflict between the influences of droplet size, variation in correlation between in vitro lipolysis or ex-vivo intestinal permeation and pharmacokinetic parameters, variation in in vivo results of solid and liquid SEDDS, and potential challenges or limitation of pharmacokinetic studies on human volunteers with orally administered SEDDS. In the past decades, hundreds of in vivo studies on SEDDS have been published. In the present study, only the relevant article on in vivo pharmacokinetic studies with orally administered SEDDS published in past 5–6 years are analyzed for an up to date compilation.